The role of inflammatory interleukins (IL-4, IL-6 & IL-10) of bladder cancer Patients (Damascus University Journal for engineering sciences, 2022)
The aim of this study was to determine Immunomolecular expression of inflammatory interleukins (IL-4, IL-6 & IL-10) by using ELISA, conventional PCR and Sequencing technologies, to acknowledge the roles of these interleukins in patients with bladder cancer in Basrah province. a controlled case study included 85 confirmed bladder cancer patients and 80 individuals as a control group. Data about age, gender, smoking, alcohol drinking, family history, occupation, residency and clinical findings for all patients with urothelial carcinoma were collected. The current study detects the molecular weight of (IL-4, IL-6 & IL-10) which were as follow (180bp, 600bp & 150bp) respectively with positive expression percentage for IL-4 (90%), IL-6 (95%) and IL-10 (60%).Conclusion: We conclude that inflammatory interleukins (IL-4, IL-6 & IL-10) are usefull for early diagnosis of bladder cancer
Keywords: interleukins; bladder cancer; PCR